Reconsideration of Patriarchal Culture Through Balancing the Dual Roles of Rifa'iyah Women in Pekalongan - Muhamad Yusrul Hana (Yinyang: Jurnal Studi Islam Gender dan Anak, 2024)
Rifa'iyah women in Pekalongan managed to break free from constraints of patriarchal culture, enabling them to actively participate in the public sphere. Over time, they have initiated changes in their understanding and interpretation of religion, adapting these to contemporary developments. Their courage and consistency in these efforts have facilitated evolutionary adaptability within the social and cultural systems of the Rifa'iyah community, ultimately realizing complete freedom for women in public activities. This study employs the historical research method, encompassing heuristics, criticism, interpretation, and historiography. The findings reveal, first, that Rifa'iyah women have driven societal change by challenging cultural norms through innovative interpretations of the Qur'an and Hadith. They also hold that their actions align with the teachings of K.H. Ahmad Rifa'i. Second, the social roles of Rifa'iyah women in Pekalongan include participation in the Wagean Islamic Study, establishing the UMRI organization, engaging in professional work, participating in activities outside the home, and being politically active. Moreover, Rifa'iyah women successfully balance dual roles by fulfilling their responsibilities as mothers and wives while collaborating with their husbands.